Enhanced Photocatalytic CO2 Reduction to CH4 Using Novel Ternary Photocatalyst RGO/Au-TNTAs - Md. Arif, Hossen; Fatema, Khatun; Riyadh Ramadhan, Ikreedeegh; Aamina Din, Muhammad; Azrina, Abd Aziz; Kah, Hon Leong; Lan, Ching Sim; Wu, Lihua; Minhaj, Uddin Monir (MDPI AG, 2023)
Abstract: Photocatalytic CO2 reduction into hydrocarbon fuels is one of the most efficient processes since it serves as a renewable energy source while also lowering atmospheric CO2 levels. The development of appropriate materials and technology to attain greater yield in CO2 photoreduction is one of the key issues facing the 21st century. This study successfully fabricated novel ternary reduced graphene oxide (RGO)/Au-TiO2 nanotube arrays (TNTAs) photocatalysts to promote CO2 photoreduction to CH4. Visible light-responsive RGO/Au-TNTAs composite was synthesized by facile electrochemical deposition of Au nanoparticles (NPs) and immersion of RGO nanosheets onto TNTAs. The synthesized composite has been thoroughly investigated by FESEM, HR-TEM, XRD, XPS, FT-IR, UV-Vis DRS, and PL analyzer to explain structural and functional performance. Under the source of visible light, the maximum yield of CH4 was attained at 35.13 ppm/cm2 for the RGO/Au-TNTAs composite photocatalyst after 4 h, which was considerably higher by a wide margin than that of pure TNTAs, Au-TNTAs and RGO-TNTAs. The CO2 photoreduction of the RGO/Au-TNTAs composite has been improved due to the combined effects of Au NPs and RGO. Due to its surface plasmonic resonance (SPR) mechanism, Au NPs play a crucial role in the absorption of visible light. Additionally, the middle RGO layers serve as effective electron transporters, facilitating better separation of electron-hole pairs. The newly constructed composite would be a promising photocatalyst for future photocatalytic applications in other fields.